Religion and Democracy in the United States : Danger or Opportunity? - Wolfe, Alan, 1942-; Katznelson, Ira (Russell Sage Foundation ; Princeton University Press, 2010)
The United States remains a deeply religious country and religion plays an inextricably critical role in American politics. Controversy over issues such as abortion is fueled by opposition in the Catholic Church and among conservative Protestants, candidates for the presidency are questioned about their religious beliefs, and the separation of church and state remains hotly contested. While the examination of religion's influence in politics has long been neglected, in the last decade the subject has finally garnered the attention it deserves. In Religion and Democracy in the United States, prominent scholars consider the ways Americans understand the relationship between their religious beliefs and the political arena. --From publisher's description.